Education about hypertension in early adults to prevent comorbid Covid-19 - Lusia Henny Mariati; Yohana Hepilita; Yuliana Reginaldis Rosali Krowa; Lidwina Dewiyanti Wea (Community Empowerment, 2023)
Young people are the target market for cigarette products because they have a long span of time consuming cigarettes. Smoking is a risk factor for hypertension. Any increase of 20 mmHg in systolic blood pressure or 10 mmHg in diastolic blood pressure can increase the risk of death from ischemic heart disease and stroke. The results of identification of unhealthy student lifestyle behavior patterns are smoking habits and lack of exercise. Identification of average blood pressure is in the pre-hypertension and first-degree hypertension categories. This shows that college students are at high risk of experiencing hypertension in advanced adulthood. Therefore the purpose of this service activity is to educate students to increase awareness in maintaining heart health and avoiding unhealthy habits. The method used is health counseling and group discussions. The results of the activity show an increase in student knowledge and demonstrate a commitment to eliminating smoking habits and lack of exercise.